L503F variant of carnitine/organic cation transporter 1 efficiently transports metformin and other biguanides. (28th June 2016) - Futatsugi, Azusa; Masuo, Yusuke; Kawabata, Shiori; Nakamichi, Noritaka; Kato, Yukio
Abstract: Objectives: Carnitine/organic cation transporter 1 (OCTN1) is involved in gastrointestinal absorption and mitochondrial toxicity of biguanides in rodents, but its pharmacokinetic roles in humans are largely unknown. The purpose of this study was to clarify the transport activities of two major OCTN1 variants, L503F and I306T, for gabapentin and three biguanide drugs, metformin, buformin and phenformin. Methods: HEK293 cells were transfected with OCTN1 gene, its variants, or vector alone, and the uptake and cytotoxicity of each drug were examined. Key findings: Buformin was identified to be an OCTN1 substrate. Uptake of biguanides, especially metformin, mediated by OCTN1 variant L503F, which is commonly found in Caucasians, was much higher than that by the wild-type transporter (WT-OCTN1). Cytotoxicity of metformin was also greater in HEK293 cells expressing the L503F variant, compared with WT-OCTN1. Uptake of gabapentin mediated by OCTN1 variant I306T, which is commonly found in both Asians and Caucasians, was lower than that by WT-OCTN1, although uptake of the typical OCTN1 substrate ergothioneine was similar. Conclusion: Organic cation transporter 1 variant L503F transports biguanides, especially metformin, more efficiently than WT-OCTN1, whereas the I306T variant transports gabapentin less efficiently than WT-OCTN1, suggesting that the common OCTN1 variants may alter pharmacokinetics of these drugs.